IDENTIFICATION ERRORS OF PROBLEM POSED BY PROSPECTIVE PRIMARY TEACHERS ABOUT FRACTION BASED MEANING STRUCTURE - Prayitno, Lydia Lia; Purwanto, Purwanto; Subanji, Subanji; Susiswo, Susiswo (Universitas Negeri Malang, 2018)
The purpose of this study was to identify problem posed by prospective teachers about addition fractions based on meaning structure. This study is a quantitative descriptive to identify errors of fraction problem posed by prospective teachers based on the meaning. 46 prospective primary teachers in 8th semester in universities at Surabaya were involved in this research. Instrument in this study is a problem posing worksheet consisting two operations on fractions. Problems posed by prospective teachers were analyzed through three stages, grouping problems based on categories, structure of meaning, and analyze the error of the problem posed. The results of data analysis indicated that: (1) on the category of questions about fractions of 93.48% for 1stoperations and 97.83% for 2ndoperation, (2) on the Non-question category about operations fraction is 6.52% for 1st operations and 1.17% for 2nd operation. Grouping problems posed by prospective teachers based on structure meaning combined category is 62.79% for 1st operations and 75.56% for 2nd operation. For category of part relationships overall is 27.91% for 1st operations and 20% for 2ndoperation, while those which not belonging to the second category are 9.3% for 1st operations and 4.44% for 2nd operation. The errors of problem posed by prospective teacher based on meaning structure are (1) not related to daily life situation, (2) illogical problem, (3) unit is not appropriate, (4) fractions incompatible with the sum operation (5) gives whole number to give meaning fraction, (6) lost information, and (7) the added result exceeds the overall concept of the fraction.